Implementación de la contabilidad comercial en créditos Jahir, del cantón Lago Agrio, provincia de Sucumbios, periodo enero a marzo del 2015 - Quisirumbay Quisirumbay, Gloria Elena (2016)
This thesis “IMPLEMENTATION OF ACCOUNTING IN CREDIT COMMERCIAL JAHIR, DEL LAGO AGRIO CANTON, SUCUMBIOS PROVINCE, JANUARY-MARCH PERIOD OF 2015”, developed with the aim of providing information relating to the economic and financial activity of the company under study, obtain information that allowed the registration of economic movements - by the application of financial accounting principles and standards in order to provide data on economic events that occurred in the company in continuous, orderly and systematic manner. Through the Implementation of commercial credits accounting Jahir, Lago Agrio Canton, January-March period of 2015, the financial situation of the company became known, through procedures that began with the lifting of inventory, general ledger, auxiliary sales constituting valid instruments to perform the accounting process and presentation of financial statements that reflect the corporate financial situation. At the end of the investigative work we present conclusions and recommendations primarily those aimed at continuing with the implementation of an organized accounting for the activity performed by the company, in this way we achieve real information in a timely manner; compliance with tax obligations and avoiding unnecessary expensive glosses.